Conformational relaxations of human serum albumin studied by molecular dynamics simulations with pressure jumps - Yesylevskyy, S.O.; Hushcha, T.O. (Вiopolymers and Cell, 2012)
Aim. In this work we developed a novel technique of obtaining the spectrum of conformational relaxations in a solvated protein using non-equilibrium molecular dynamics simulation. Methods. Structural relaxations in the protein are initiated by the abrupt jump of pressure in the NPT simulations. The change of the protein volume after the jump is monitored and the Maximum Entropy Method is used for spectral decomposition of the volume relaxation curve. The human serum albumin (HSA) is used as a test case. Results. The obtained relaxation spectrum of HSA contains one component attributed to the bulk water and five components caused by the relaxations of the protein globule and its hydration shell. All relaxation components are in good agreement with the available experimental data obtained by the time-resolved spectroscopy and the broadband acoustic spectroscopy of HSA. Conclusions. The developed technique allows obtaining spectra of conformational relaxations of soluble proteins in a range of time scales from ~0.1 ps to ~50 ns utilizing single non-equilibrium molecular dynamics simulation.
Keywords: protein relaxations, molecular dynamics, maximum entropy method, pressure jump, HSA. Мета. Розробка методики, що дозволяє отримувати спектри конформаційних релаксацій сольватованого білка методом нерівноважної молекулярної динаміки. Методи. Структурну релаксацію білка ініціювали різкою зміною тиску у процесі розрахунку в NPT- ансамблі. Проведено спектральну декомпозицію кривої зміни об’єму білка після стрибка тиску методом максимальної ентропії. Результати. Одержаний спектр релаксацій містить один компонент, що належить до чистої води, і п’ять компонентів, віднесених до білка та його гідратної оболонки. Конформації всіх компонентів відповідають структурам, отриманим методами оптичної і акустичної спектроскопії. Висновки. Розроблена методика дозволяє розраховувати спектри структурної релаксації сольватованих білків у діапазоні часів від ~0,1 пс до ~50 нс з однієї траєк- торії, одержаної методом нерівноважної молекулярної динаміки.
Ключові слова: релаксація білка, молекулярна динаміка, метод максимальної ентропії, стрибки тиску, сироватковий альбумін людини. Цель. Разработка новой методики получения спектра конформационных релаксаций сольватированного белка методом неравновесной молекулярной динамики. Методы. Структурную релаксацию белка инициировали резким изменением давления в процессе расчета в NPT-ансамбле. Проведена спектральная декомпозиция кривой изменения объема белка после скачка давления методом максимальной энтропии. В качестве тестового объекта использован сывороточный альбумин человека. Результаты. Полученный спектр релаксаций содержит один компонент, принадлежащий чистой воде, и пять компонентов, относящихся к белку и его гидратной оболочке. Конформации всех компонентов соответствуют таковым, полученным методами оптической и акустической спектроскопии. Выводы. Разработанная методика позволяет рассчитывать спектры конформационных релаксаций сольватированных белков в диапазоне времен от ~0,1 пс до ~50 нс из единственной траектории, вычисленной методом неравновесной молекулярной динамики.
Ключевые слова: релаксация белка, молекулярная динамика, метод максимальной энтропии, скачки давления, сывороточный альбумин человека.